Limitation in the Photosynthetic Acclimation to High Temperature in Canopy Leaves of Quercus serrata - Yamaguchi, Daisuke P.; Mishima, Dai; Nakamura, Kozue; Sano, Junji; Nakaji, Tatsuro; Hiura, Tsutom; Hikosaka, Kouki (Frontiers in Forests and Global Change, 2019)
As temperature dependence in many biological precesses is generally a bell-shaped curve, warming may be benefitial at cooler climate but deterimental at warmer climate. Although warming responses are expected to vary between different temperature regimes even in the same species, such variations are poorly understood. We established open-top canopy chambers, in which average daytime leaf temperature was increased by ca. 1.0°C, at the canopy top of Quercus serrata in a deciduous forest in high (HL) and low (LL) latitude sites and studied temperature dependence of photosynthesis in the leaves across seasons. In control leaves, photosynthetic rates were higher in LL than in HL. Reponse to warming was different between HL and LL; an increase in growth temperature increased photosynthetic rates at higher leaf temperatures in HL but decreased in LL. Lower photosynthetic rate in the warming treatment in LL was partly explained by lower leaf mass per area and leaf nitrogen content per unit leaf area. Optimal temperature that maximizes photosynthetic rate (Topt) linearly increased with increasing growth temperature (GT) in HL, whereas it was saturating against GT in LL, suggesting that Topt in Q. serrata has an upper limit. The variation in Topt was explained by the activation energy of the maximum carboxylation rate (EaV). Our results suggest an upper limit in temperature acclimation of photosynthesis, which may be one of the determinants of southern limitation of the distribution.